A novel host shift and invaded range of a seed predator, Acanthoscelides macrophthalmus (Coleoptera: Chrysomelidae: Bruchinae), of an invasive weed, Leucaena leucocephala - Midori Tuda (2018)
An endophagous seed predator, Acanthoscelides macrophthalmus (Coleoptera: Chrysomelidae: Bruchinae), utilizes Neotropical Leucaena (Fabaceae: Mimosoideae). One of its hosts, Leucaena leucocephala, is a fast-growing nitrogen-fixing tree that serves as a multipurpose beneficial plant but eventually becomes an aggressive invader where it was introduced. Herein, we report A. macrophthalmus invasion of the Far East, South Asian tropics and subtropics (Japanese Pacific Islands, Taiwan, Southern China, Northern Thailand and Southern India). Of other field-collected mimosoid legumes, an introduced tree, Falcataria moluccana, in Taiwan was found to be used by the seed predator. Conversely, our published work review revealed that the seed predator had retained high host specificity to Leucaena species in its native and introduced regions. Acanthoscelides macrophthalmus was able to utilize aphagously postharvest mature seeds for oviposition and larval development, which is a trait of post-dispersal seed predators. We confirmed that A. macrophthalmus that was reared on L. leucocephala was able to utilize F. moluccana as well. Although the relatively high host specificity of the oligophagous beetle is suitable for controlling the weedy L. leucocephala, the potential host range expansion confirmed by this study must be cautioned. © 2009 The Entomological Society of Japan.